Case report of massive hemoptysis in pregnancy requiring veno‐venous extracorporeal membrane oxygenation. Issue 12 (4th September 2019) - Stiff, Alyssa; Harrison, Rachel; Palatnik, Anna
Abstract: Hemoptysis in pregnancy is rare and can be life‐threatening. This case describes management of hemoptysis in pregnancy requiring veno‐venous extracorporeal membrane oxygenation (VV‐ECMO). The patient presented with massive hemoptysis in respiratory failure at 26 weeks gestation. VV‐ECMO was utilized for maternal stability due to severe hypoxia from lung parenchymal damage. An extensive work‐up for hemoptysis returned negative except for an elevated Bordetella pertussis IgG antibody. The patient was delivered via cesarean section with a complicated post‐partum course. She and the infant were discharged in stable condition after long hospital stays. Prior publications describing VV‐ECMO use in pregnancy are limited to treatment of respiratory infections such as influenza or pneumonia. This case is the first in the literature to describe VV‐ECMO utilization for hemoptysis in pregnancy, specifically, and demonstrates its significant benefit in cases of respiratory failure due to hemoptysis.